ACCOUNTING INFORMATION SYSTEMS - Gelinas, Ulric J., author; Dull, Richard B., author; Wheeler, Patrick R., author (South Melbourne, Victoria : Cengage Learning Australia, 2018)
"Today's accounting professionals are challenged to identify enterprise risks and provide quality assurance for a company's information systems. Accounting Information Systems, 11th International Edition, focuses on three critical accounting information systems in use today: enterprise systems; e-Business systems; and controls for maintaining those systems. Students will easily grasp even the most challenging topics as they explore today's most intriguing AIS topics relative to business processes, information technology, strategic management, security, and internal controls. The 11th International Edition provides students with the tools for organising and managing information to help them succeed and protect the integrity of their employer's information system."